El desarrollo de la coordinación y su incidencia en la técnica para la conducción del balón en niños de 8 y 9 años de edad. Propuesta de una guía didáctica en el fútbol - Tanguila Narváez, Matías Efraín (2016)
This research entitled: “THE DEVELOPMENT OF COORDINATION AND ITS INCIDENCE IN THE TECHNIQUE FOR BALLON DRIVING IN CHILDREN OF 8 AND 9 YEARS OF AGE. PROPOSAL FOR A DIDACTIC GUIDE TO FOOTBALL” It focuses on investigating the problem detected: How to create a Didactic Guide based on coordination exercises for the development of the technique of conduction of the ball in the Physical Education classes football for children 8 and 9 years of age in the Educational Unit "Ávila",?. A non-experimental study was carried out with the purpose of designing a Didactic Guide from exercises of the coordinating capacities to improve the technique in the conduction of the ball of the children of 8 and 9 years of age, who receive Physical Education classes in the Educational Unit "Ávila", The general objective was: To design a Didactic Guide based on exercises of the coordination capacities for the development of the technique of conduction of the ball in the classes of Physical Education of soccer for children of 8 and 9 years of age subject To research. Methods and research techniques were used among them, the scientific, deductive, inductive and statistical, that allowed to base the object and field of the investigation, determining the existing regularities in the theory and the practice of the studied Physical Education; As well as the processing of the obtained data. The sample was represented by 2 teachers and 80 children 8 and 9 years old. We conclude that there is a need for the design of the Didactic Guide, based on the diagnosis, among others, that the coordinating capacity and its relation with the technique of conducting the balloon at these ages in the classes of Physical Education, Has been little studied in Primary Education in our country. In the development of this coordinating capacity, they do not correspond to their potentialities; So that the Didactic Guide was conceived with interrelated methodological phases and requirements, which allowed the direction of the development of the coordinating capacity and the technique for the conduction of the ball. The results reveal the feasibility of the proposal, manifested in the positive changes in the dimension studied as a scientific product designed.